Determinants of Operational Performance in Maritime Livestock Transport: A Mixed-Methods SEM–PLS Study from Indonesia - Achmad Bashori Bashori; Ihsan Ahda Tanjung; Innayatur Robbany; Sahar Saleh; Fahmi Umasangadji; Saidal Siburian (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
Livestock transportation by sea plays an important role in Indonesia's national cattle supply chain, but to date, it still faces challenges in the form of variability in service quality, driver competence, and the lack of digital monitoring technology on board ships. This study aims to identify the factors that influence the operational performance of government-owned livestock ships (Camara Nusantara 1 to 6) by integrating service quality, technological readiness (based on perception), and the role of crew members/kleder into a single integrated analytical model. A mixed-methods approach was used in this study. The quantitative stage used Structural Equation Modelling–Partial Least Squares (SEM–PLS) with 34 respondents, while the qualitative stage was conducted through in-depth interviews with officials from the Directorate of Traffic and Sea Transportation, Ministry of Transportation. Regulatory variables were measured but excluded from the structural model due to multicollinearity with service variables. The results showed that service quality had a significant effect on operational performance. At the same time, technology, although not yet implemented on livestock ships was the strongest predictor, reflecting stakeholders' expectations for future digitalisation. The role of kleders did not have a statistically significant effect, even though they played a major role in manually monitoring livestock conditions. Qualitative findings reinforce these results by demonstrating inconsistencies in kleders' competencies, limitations in technological infrastructure, and variations in operational implementation between regions. This study contributes to the development of marine livestock logistics systems in Indonesia, while also providing policy recommendations to improve efficiency, safety, and livestock welfare.